PENERAPAN MODEL POE (PREDICT-OBSERVE-EXPLAIN) DENGAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR IPA DAN RETENSI SISWA DI SMP - Ria Inayatush Shofiah; Singgih Bektiarso; Bambang Supriadi (FKIP Universitas Jember, 2017)
In the process of learning science students are given the opportunity to think aboutand define the concept of its own. This had resulted in the concept of learned students tendnot to last long. So the researchers chose a learning model POE (predict-observe-explain)with the experimental method, which aimed to assess the influence of learning model POE(Predict-Observe-Explain) against the results of the experiment method accompanied bystudent learning and retention results of student learning in junior high school. The type ofthis research was experiments research with post test only control group design. Thetechnique of data collection in this research was the study results and data retention ofstudents. The data analysis techniques was using SPSS 17, student learning outcomes dataobtained value of 0.005<0,05 which show that there was a significant difference betweenthe results of science learning students in class experiments and control classroom. Whilethe value of retention in experimentsclass had increased 2.78% and the control class haddecreased 16.6%. Based on the research results, it can be concluded that the results of theclass experiment of very good as well as the memory of students in the class of experimentshad increase.Keywords: POE (Predict-Observe-Explain), experiment method, retention